Food allergy identification. - Chen, Bryan Siming. (2013)
Creating an awareness campaign to address the issue of food allergy in Singapore. Done through raising awareness and educating food vendors and the general public. Designed collateral would allow affected people to better communicate their allergies to food vendors and avoid eating food they are allergic to.